2014
DOI: 10.2478/amm-2014-0069
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Selected Alloying Elements on the Mechanical and Electrical Aluminium Properties

Abstract: Modern industry expects aluminum products with new, unusual, and well-defined functional properties. Last years we are able to notice constant development of aluminium alloys. In food industry, power engineering, electrical engineering and building engineering, flat rolled products of 1XXX series aluminium alloys are used.8XXX series alloys registered in Aluminium Association during last 20 years may be used as an alternative. These alloys have very good thermal and electrical conductivity and perfect technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…On the other hand, the Fe solute level after the thermal holding treatment was evaluated by EC measurements. Based on the relationship between the EC and concentration of the alloying elements in the solid solution, a quantitative estimation of the Fe solute content was calculated according to the following equation: 29,30 …”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the Fe solute level after the thermal holding treatment was evaluated by EC measurements. Based on the relationship between the EC and concentration of the alloying elements in the solid solution, a quantitative estimation of the Fe solute content was calculated according to the following equation: 29,30 …”
Section: Resultsmentioning
confidence: 99%
“…as well as presence of obstacles such as other phase's particles, porosity, grain boundaries etc. Mamala et al [10] have found that iron strongly affects the conductivity of the α-Al solid solution, however it is not so harmful when bounded outside the solid solution. This conclusion is in accordance with our investigations, in which iron is present mainly in form of intermetallic phases and is not determining for the electrical properties.…”
Section: Discussionmentioning
confidence: 99%
“…luminum alloys find application in diverse fields owing to their high strength-to-weight ratio, low cost, and ease of fabrication [1][2][3]. Substituting the base aluminum alloys with particulate composites has the advantage of improving the mechanical strength parameters without seriously disturbing the thermal and electrical conductivities and other properties A [4][5][6][7]. The common reinforcement particles used in AMMCs are graphite, SiO 2 , SiC, Al 2 O 3 and B 4 C used in small percentages of about 2 to 8% [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%